+0  
 
0
305
6
avatar+2493 

Fot an experiment, a liquid is kept in cold storage at a temperature of 20 degrees Fahrenheit(°F). The liquid is removed from cold storage and is warmed at a constant rate of 3°F per hour. Which of the following represents the temperature of the liquid, in degrees Celsius(°C), t hours after it has been removed from cold storage ?

(Note:°C=5/9(°F-32).) 

 

A)5/3t-20/3

B)5/3t-188/9

C)5/9t-20/3

D)27/5t+68

E)3t+20

Solveit  Jan 3, 2016
edited by Solveit  Jan 3, 2016

Best Answer 

 #6
avatar+78575 
+10

The temperature in F after t hours = 3t + 20

 

F →  C    ..... C =   (F - 32)/ (9/5)

 

So ....the temperature in  C  after t hours   = 

 

( 3t + 20 - 32)/ (9/5)  = ( 3t - 12) / (9/5)  = (5/9)(3t - 12)  = (5/9) * 3(t - 4)  =  (5/3)(t - 4)  =  (5/3)t - 20/3

 

 

 

cool cool cool

CPhill  Jan 3, 2016
Sort: 

6+0 Answers

 #1
avatar+2493 
+5

I found the answer (A)

Solveit  Jan 3, 2016
edited by Solveit  Jan 3, 2016
 #2
avatar
0

E     E   E   EE   EEEE   E   'E'

Guest Jan 3, 2016
 #3
avatar+2493 
0

Why (E) ?

Solveit  Jan 3, 2016
 #4
avatar
+5

The sample STARTS at 20 degrees so the temperature is  20 + ?

Every hour it warms up an ADDITIONAL   3 degrees  so the temperature after  't' hours will be INCREASED  3 x t

It STARTED at 20 degrees    so  add both of the terms together to get the temperature of the sample  20 + (3 x t)

or  20 + 3t     Rewritten :  3t + 20

 

Now I re-read the question: it asks for Celcius

Convert to Celcius   5/9 (3t +20) -32 )

15/9t - 60/9

5/3t - 20/3

 

So YOU were RIGHT !   I was WRONG....sorry....I misread the question!!!

Guest Jan 3, 2016
edited by Guest  Jan 3, 2016
 #5
avatar+2493 
+5

Yea you right but you get it on °F but i need on °C so i put it into °C=5/9(°F-32) and get (A)

Solveit  Jan 3, 2016
 #6
avatar+78575 
+10
Best Answer

The temperature in F after t hours = 3t + 20

 

F →  C    ..... C =   (F - 32)/ (9/5)

 

So ....the temperature in  C  after t hours   = 

 

( 3t + 20 - 32)/ (9/5)  = ( 3t - 12) / (9/5)  = (5/9)(3t - 12)  = (5/9) * 3(t - 4)  =  (5/3)(t - 4)  =  (5/3)t - 20/3

 

 

 

cool cool cool

CPhill  Jan 3, 2016

4 Online Users

avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details